Distribution and Clinical Utility of the Kidney Disease Improving Global Outcomes Chronic Kidney Disease Risk Classification in Patients Undergoing Atrial Fibrillation Ablation - Hironori Ishiguchi; Yasuhiro Yoshiga; Shintaro Hashimoto; Masakazu Fukuda; Goki Nakashima; Masafumi Fujinaka; Masaki Shibuya; Takuya Omuro; Shigeki Kobayashi; Motoaki Sano (Journal of the American Heart Association, 2026)
Background Chronic kidney disease (CKD) is a key component of the cardiovascular–kidney–metabolic framework. However, in patients undergoing atrial fibrillation ablation, the distribution of CKD across Kidney Disease: Improving Global Outcomes risk categories and its prognostic value remain unclear. Methods Patients undergoing atrial fibrillation ablation with preprocedural urinalysis were studied. Patients were classified into Kidney Disease: Improving Global Outcomes CKD risk categories (low, moderate, high, very high) using the estimated glomerular filtration rate and predicted urine albumin–creatinine ratio derived from dipstick proteinuria. We compared postdischarge heart failure hospitalization incidence across risk categories and assessed cardiovascular–kidney–metabolic multimorbidity (all 3 components present) and the use of kidney‐protective therapies. Results Among 942 patients, 505, 277, 118, and 42 were classified as low, moderate, high, and very high risk, respectively; 46.3% met the Kidney Disease: Improving Global Outcomes definition of CKD (≥moderate). Over a median follow‐up of 5.1 years (interquartile range, 3.1–7.1), 72 patients (7.6%) were hospitalized for heart failure. Heart failure hospitalization incidence increased across CKD risk categories ( p